Two small-molecule activators share similar effector sites in the KCNQ1 channel pore but have distinct effects on voltage sensor movements - Chen, Lei; Peng, Gary; Comollo, Thomas W.; Zou, Xinle; Sampson, Kevin J.; Larsson, H. Peter; Kass, Robert S. (Frontiers in Physiology, 2022)
ML277 and R-L3 are two small-molecule activators of KCNQ1, the pore-forming subunit of the slowly activating potassium channel IKs. KCNQ1 loss-of-function mutations prolong cardiac action potential duration and are associated with Long QT Syndrome, which predispose patients to lethal ventricular arrhythmia. ML277 and R-L3 enhance KCNQ1 current amplitude and slow deactivation. However, the presence of KCNE1, an auxiliary subunit of IKs channels, renders the channel insensitive to both activators. We found that ML277 effects are dependent on a number of residues in the KCNQ1 pore domain. Some of these residues are also necessary for R-L3 effects. These residues form a hydrophobic pocket located between two adjacent KCNQ1 subunits, where KCNE1 subunits are thought to dwell, thus providing an explanation for how KCNE1 render the IKs channel insensitive to these activators. Our experiments showed that R-L3’s effect on voltage sensor movement during channel deactivation was much more prominent than that of ML277. Simulations using a KCNQ1 kinetic model showed that the effects of ML277 and R-L3 could be reproduced through two different effects on channel gating: ML277 enhances KCNQ1 channel function through a pore-dependent and voltage sensor-independent mechanism, while R-L3 affects both channel pore and voltage sensor.